1997
DOI: 10.1046/j.1570-7458.1997.00110.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in defences of the plant Barbarea vulgaris and in counteradaptations by the flea beetle Phyllotreta nemorum

Abstract: Several sorts of variation in the interaction between the insect, Phyllotreta nemorum L. (Coleoptera: Chrysomelidae: Alticinae), and the plant, Barbarea vulgaris R.Br. (Brassicaceae), have been discovered: 1) genetic differences in the levels of defences in the plant, 2) genetic differences in the ability of insects to cope with the plant defences, 3) seasonal variation in levels of defences in the plant, and 4) differences between leaf types in levels of defences.Two plant accessions were suitable for larval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
107
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(108 citation statements)
references
References 15 publications
1
107
0
Order By: Relevance
“…Nielsen (1997a) found that different types of B. vulgaris arcuata differ dramatically in their resistance to the flea beetle, Phyllotreta nemorum. These plant populations have been described as a 'G-type', with glabrous leaves and a 'P-type', which has pubescent leaves.…”
Section: Resistance Of Barbarea Species To Crucifer Specialistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nielsen (1997a) found that different types of B. vulgaris arcuata differ dramatically in their resistance to the flea beetle, Phyllotreta nemorum. These plant populations have been described as a 'G-type', with glabrous leaves and a 'P-type', which has pubescent leaves.…”
Section: Resistance Of Barbarea Species To Crucifer Specialistsmentioning
confidence: 99%
“…The P-type is susceptible to the flea beetle, whereas the G-type is generally resistant. In addition to these genetic differences in levels of defense, Nielsen (1997a) found that seasonal variation and differences between leaf type occur. Subsequent work revealed the existence of populations of the flea beetle that could deal with this plant resistance to feed successfully on the G-type of the subspecies (Nielsen, 1997b).…”
Section: Resistance Of Barbarea Species To Crucifer Specialistsmentioning
confidence: 99%
“…Therefore, variation in plant traits may significantly influence ecosystem biodiversity (Dungey et al 2000, Hochwender and Fritz 2004, Wimp et al 2005, Poelman et al 2008c (Dungey et al 2000, Johnson and Agrawal 2005, Bangert et al 2006. Variation in phytochemistry of plant genotypes may include quantitative or qualitative differences in only a few chemical compounds, and phytochemical composition may be heritable (van Dam and Vrieling 1994, Nielsen 1997, van Leur et al 2006). Intraspecific differences in foliar chemical profiles, i.e., the qualitative composition of the mix of phytochemicals, may have extensive consequences for ecosystem biodiversity and especially affect species that are in close reciprocal interaction with plants, such as herbivorous insects (Johnson and Agrawal 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas parasitism on Barbarea is higher than on Sinapis at any particular moment (orange bars higher than brown ones), the parasitism of the cohort of flea beetles on Barbarea across the whole season is lower than on Sinapis Evol Ecol (2011) 25:485-498 487 de de Jong and Nielsen 2002;Renwick 2002). Resistant flea beetles are relatively rare, which has led to the hypothesis that the use of Barbarea represents a hostrange expansion of P. nemorum (Nielsen 1997). The genotype of B. vulgaris ssp.…”
Section: Case Study In Denmarkmentioning
confidence: 99%
“…nemorum has one generation per year in Denmark, and adults overwinter in diapause in the soil. Eggs are laid in the soil close to the host plants, and newborn larvae climb into a nearby plant, after which they start mining its leaves (Nielsen 1997). The larvae of P. nemorum are known to be attacked by at least five hymenopteran parasitoids (Ulber and Williams 2003), including Diospilus morosus Reinhardt (Braconidae) and Aneuclis brevicauda Thomson (Ichneumonidae).…”
Section: Case Study In Denmarkmentioning
confidence: 99%